The design of frontier spaces : control and ambiguity - Loeb, Carolyn. Luescher, Andreas (Design and the built environment series., 2021)
In a globalizing world, frontiers may be in flux but they remain as significant as ever. New borders are established even as old borders are erased. Beyond lines on maps, however, borders are spatial zones in which distinctive architectural, graphic, and other design elements are deployed to signal the nature of the space and to guide, if not actually control, behavior and social relations within it. This volume unpacks how manipulations of space and design in frontier zones, historically as well as today, set the stage for specific kinds of interactions and convey meanings about these sites